The Effectiveness of Enforcement of Light Crime Laws in Preventing Liquor Circulation by the Jombang Police Samapta Unit - Hasibuan, Samuel Junrichky (Advances in Police Science Research Journal, 2024)
The crime of selling liquor is one of the public crimes that is prohibited in several regions in Indonesia. Samapta plays an important role in preventing the distribution of alcoholic beverages by means of preventive and repressive law enforcement and also with the help of reports from the public. This analysis highlights the effectiveness of law enforcement for minor criminal offenses in preventing the distribution of liquor with the aim of finding out and also analyzing the implementation and factors that influence enforcement by the Jombang Police Samapta Unit with the hope that there will be changes regarding law enforcement for minor criminal offenses selling illegal liquor in the future.